2007
DOI: 10.5603/arm.27997
|View full text |Cite
|
Sign up to set email alerts
|

Rola eotaksyn w patofizjologii astmy

Abstract: Astma wiąże się z napływem eozynofilów do dróg oddechowych. Eozynofile odgrywają ważną rolę w patogenezie tej choroby. Interleukina-5 jest głównym czynnikiem regulującym proliferację, dojrzewanie i dystrybucję eozynofilów, mimo że ostatnie badania sugerują, że poza IL-5 w patogenezie astmy może uczestniczyć eotaksyna. Eotaksyna jest CC chemokiną po raz pierwszy odkrytą w płynie z płukania oskrzelikowo-pęcherzykowego u świnki morskiej. Eotaksyna łączy się selektywnie z receptorem CCR3 obecnym na eozynofilach, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…This observation is likely due to the reduction in IL-4, IL-13, and VEGF, which facilitates transmigration of circulating eosinophils into the asthmatic lungs (36,37). Concomitantly, normalization of the CCL11 level by the therapy likely contributed to blockade of eosinophil recruitment, given that the chemokine serves as a primary chemoattractant to eosinophils (37,38). It has been previously reported that eosinophil-deficient mice are notably protected from airway collagen deposition and smooth muscle accumulation despite the challenge by OVA (39).…”
Section: Discussionmentioning
confidence: 99%
“…This observation is likely due to the reduction in IL-4, IL-13, and VEGF, which facilitates transmigration of circulating eosinophils into the asthmatic lungs (36,37). Concomitantly, normalization of the CCL11 level by the therapy likely contributed to blockade of eosinophil recruitment, given that the chemokine serves as a primary chemoattractant to eosinophils (37,38). It has been previously reported that eosinophil-deficient mice are notably protected from airway collagen deposition and smooth muscle accumulation despite the challenge by OVA (39).…”
Section: Discussionmentioning
confidence: 99%